Edukasi Kanker Serviks dan Efektivitas Vaksin HPV Sejak Dini di SMAN 2 Pekanbaru - Muhammad Faisal; Alief Dhuha; Mega Pratiwi Irawan; Sellia Juwita; Putri Wulandini (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
In 2013, the number of cervical cancer cases in Riau Province reached 894 cases. In 2020, RSUD Arifin Achmad Riau Province reported the cervical cancer was the third rank below breast and ovarian cancer. Cervical cancer has major risk factor named by HPV virus. HPV vaccine has been reported to adequate to eliminate HPV viruses. The Indonesian government has provided the health facilities to decrease cervical cancer sufferers by providing HPV vaccines. However, vulnerable women are not ready to be vaccinated. Education level is one of the factors. Hence, we try to intervene the mind of SMAN 2 Pekanbaru female students by offer early knowledge regarding the risk factors of cervical cancer, how to prevent as well as socialize HPV vaccine effectivity and safety. Educational and outreach activities were carried out by material presentation method by a direct meeting which interactive and educative. Feedback data collection from the activities was given through the Google Form platform. This activity was held on Monday, 22nd November 2021 at 09.00 – 10.35 West Indonesian Time, joined by 20 female students of SMAN 2 Pekanbaru which included three grade levels, X, XI, and XII class. According to the results of the questionnaire, we obtained the improvement of cervical cancer and HPV vaccine information. Moreover, this activity upgraded the awareness of cervical cancer prevention, by as much as 25% (N=12). We may conclude that education on cervical cancer is tremendously important to young women as our effort to decrease cervical cancer cases in the future.